Analysis of vegetative seed production alternatives of Arracacia xanthorrhiza Bancroft in Tolima, Colombia - Atencio Solano, Liliana Margarita; Villamil Carvajal, Jorge Enrique; Garnica Montaña, Johanna Paola; Martínez Reina, Antonio María (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The propagation of plant material in the cultivation of arracacha is commonly carried out vegetatively through asexual seed, this activity has allowed its multiplication and conservation over time. The plant material available is of low quality, affecting the development and potential yield of the crop and therefore the income of the producer. The objective of the research was to comparatively analyze two arracacha seed production technologies: Local technology and Agrosavia technology. The information for local technology was obtained from surveys applied to farmers and the selection was made through the deterministic sampling technique, and for the Agrosavia technology data and production costs were recorded in research lots on a commercial scale. Descriptive statistics and calculation of the economic return indicators were applied for the two situations. The results show that the use of quality seed allows obtaining a higher production of seeds (251,559 unit ha-1) and tuberous roots (25,875 kg ha-1), being superior to local technology by 14% and 28%, respectively. Thus, the arracacha producer acquires greater economic efficiency by obtaining a lower unit cost per kilo produced and a better net income with a marginal rate of return of 316.45. The results achieved are useful for producers, companies, and entities that wish to produce quality seed and support the production system of arracacha in Colombia.